Customer Satisfaction as the Mediating Variable Between Customers Value and Customer Loyalty - Astari, Kiptya Nur; Rahayu Silintowe, Yunita Budi; Susanto, Annie (Indonesian Journal Publisher, 2025)
Growth in the cosmetics industry has encouraged the emergence of various beauty products in the Indonesian market, including beauty clinics. Beauty clinics offer beauty products and special treatments, ranging from face to whole-body treatments. The factors that encourage the customers to use a beauty clinic’s products are customers values. This research aimed at analyzing the impact of customers values on customers loyalty mediated by customers satisfaction variable. The sampling method in this research was simple random sampling, with 188 respondents, who were the customers of Natasha Skin Clinic Center, as the research objects. The data were analyzed using path analysis method. The result revealed that customers values significantly influenced customers satisfaction, and customers satisfaction significantly influenced customers loyalty. Customers values significantly influenced customers loyalty only if it was mediated by customers satisfaction, and did not directly influence customers loyalty